Oxidation of SO2 and NO by epoxy groups on graphene oxides: the role of the hydroxyl group1. Issue 29 (27th April 2015) - Cen, Wanglai; Hou, Meiling; Liu, Jie; Yuan, Shandong; Liu, Yongjun; Chu, Yinghao
<x xml:space="preserve">Abstract</x> Hydroxyl groups facilitate the oxidation of SO2 and NO by epoxy groups on carbon materials.